Case Report: Small intestinal metastatic breast cancer: A case report and literature review - Li, Yishan; Zhang, Lianru; Yu, Huiping; Xin, Xiaoyan; He, Jian; Yao, Yongzhong; Liu, Baorui; Li, Rutian; Xie, Li (Frontiers in Oncology, 2022)
Breast cancer is considered a malignant tumor with the highest incidence among women and is prone to develop distant metastasis. Small intestinal metastasis of breast cancer, however, is relatively rare. This case report describes a 49-year-old Chinese female patient who presented with small intestinal obstruction and was diagnosed with lobular breast cancer with small intestinal and contralateral breast metastasis. Clinical manifestations, clinicopathological features and potential mechanisms of metastasis, along with diagnosis and treatment, are discussed with a review of the relevant literature. Although small intestinal metastasis is rare in breast cancer, we should keep high alert on the possibility of gastrointestinal metastasis when treating lobular breast cancer patients.